The determinants of companies' levels of integration: Does one size fit all?. Issue 3 (April 2019) - Busco, Cristiano; Malafronte, Irma; Pereira, John; Starita, Maria Grazia
Abstract: This article extends current knowledge in the field of integrated thinking and reporting (ITR) by providing new empirical evidence on the nature and determinants of companies' levels of integration (i.e. ITR levels). Based on legitimacy theory and stakeholder theory, we empirically investigate companies' levels of integration and examine the drivers of different ITR levels. Our results suggest that companies' levels of ITR, namely Holistic, Integrated, Conservative, and Minimalist, are related to company characteristics and tend to remain consistent over time exhibiting routine and imitation. Companies with greater size, leverage, bigger board size and meetings, as well as companies operating in sensitive industries and with higher environmental performance are more likely to exhibit a Holistic or Integrated level of integration, while Minimalist and Conservative levels are driven by the same variables in opposite direction. Furthermore, at country level, economic growth, market performance, citizens freedom and lower environmental performance significantly contribute to higher integration. These results could drive companies' choices alongside policymakers' initiatives, by identifying which levers should be pulled to achieve the desired level of integration, and suggest the need for a tailored approach rather than a one size fits all within the debate on the future developments of ITR.